Household waste separation intention and the importance of public policy - Bing Chen; Jiwon Lee (International Trade, Politics and Development (ITPD), 2020)
Purpose - The key challenge that urban cities in most developing and transitional economies is confronting is municipal solid waste (MSW) management. Waste separation is a critical component to successful recycling management in terms of enhancing the quality of recyclables, reducing MSW and optimizing incineration. The urge to actualizing sustained waste separation behavior has been hindered by potential barriers. This study aims to examine the influences of external and internal stimuli of targeted households' waste separation intention in parts of China. Design/methodology/approach - A multifactor framework predicting the process that leads to waste separation attitude and behavioral intention is proposed. SEM analysis is conducted in SmartPLS based on 371 survey questionnaires collected in Nanning city in China. Findings - Policy regulation is the biggest determinant of attitude among external stimuli, while awareness of consequence has the strongest relationship with an attitude among internal stimuli. Facilitating conditions, subjective norms and moral norms are all significant predictors of attitude. As a result, increasing positive attitude leads to enhance waste separation lifestyle. Research limitations/implications - This study adopts a cross-sectional design to investigate the waste separation intention of local households. Data collection is restricted to one point in time for every individual. A mixed method is recommended. Quantitative research can examine variables provided in existing literature with numerical analysis. Qualitative research might be helpful to identify other unknown factors. Also, the survey questionnaires employ a self-reported manner, and respondents might be overrating to avoid embarrassment. Practical implications - Future research is recommended to engage observation at houses or at the wastecollecting points for actual waste separation behavior. Moreover, this study measures intention toward household waste separation, but whether this intention will eventually lead to waste separation behavior is not a guarantee. Future study is recommended to examine whether intention translates into actual waste separation behavior. Originality/value - Emphasizing the importance of policy element as a direct influence toward attitude, this paper focuses on the waste separation attitude accumulated from external and internal stimuli, and, concurrently, waste separation behavioral intention is influenced by accumulated attitudes. The study provides relevant policy development information of three Asian countries to enhance their present and future policy directions for a sustainable household waste separation management process.
Keywords: 330; Municipal solid waste; Household waste separation intention; External stimuli; Internal stimuli; Municipal governments